Influence of Hydroxyapatite Coating for the Prevention of Bone Mineral Density Loss and Bone Metabolism after Total Hip Arthroplasty: Assessment Using (18)F-Fluoride Positron Emission Tomography and Dual-Energy X-Ray Absorptiometry by Randomized Controlled Trial - Tezuka, Taro (Biomed Res Int, 2020)
BACKGROUND: Hydroxyapatite- (HA-) coated implants tend to achieve good osteoinductivity and stable clinical results; however, the influence of the coating on the prevention of bone mineral density (BMD) loss around the implant is unclear. The purpose of this randomized controlled trial was to evaluate the effectiveness of HA-coated implants for preventing BMD loss and to determine the status of bone remodeling after total hip arthroplasty (THA), making comparisons with non-HA-coated implants. METHODS: A total of 52 patients who underwent primary THA were randomly allocated to HA and non-HA groups. BMD was measured by dual-energy X-ray absorptiometry (DEXA) at 1 week postoperation to form a baseline measurement, and then 24 weeks and 48 weeks after surgery. The relative change in BMD was evaluated for regions of interest (ROIs) based on the Gruen zone classifications. (18)F-fluoride positron emission tomography (PET) was performed at 24 weeks postsurgery, and the maximum standardized uptake values (SUV(max)) were evaluated in the proximal (HA-coated) and distal (non-HA-coated) areas in both groups. RESULTS: There were significant differences in BMD loss in ROIs 3 and 6 (p = 0.03), while no significant difference was observed in ROI 7 at either 24 or 48 weeks postsurgery. There was no significant correlation between PET uptake and BMD (24 or 48 weeks) in either group. CONCLUSION: The influence of a HA coating in terms of BMD preservation is limited. No significant correlation was found between BMD and SUV(max) measured by PET, either with or without the use of a HA coating.